Western aid and trade policy trends - Siegfried Schultz (Intereconomics, 1985)
The Third Development Decade of the United Nations opened with a promising outlook for the developing countries. The economic situation of the OECD countries had improved during 1979 and the “North-South dialogue” seemed to be making progress. But the further course of 1980 and the subsequent years revealed that the extent and long-term effects of the slump in world economic activity had been seriously underestimated. A large number of developing countries continue to be heavily dependent on development aid. The following article outlines current trends in aid and the likely prospects for the future.
Keywords: 330; North-South Relations